Evaluation of chemical events at Army chemical agent disposal facilities - National Research Council (U.S.). Committee on Evaluation of Chemical Events at Army Chemical Agent Disposal Facilities; ebrary, Inc. (Washington, D.C. : The National Academies Press, 2002)
"The National Research Council was asked by the Army to form a special, ad hoc committee to investigate whether incidents involving chemical warfare material stored, processed, and destroyed at the two operational Army chemical demilitarization sites provide useful information for the safe operation of future sites"--P. 1.
Includes bibliographical references (p. 57-58).
Electronic reproduction.
Financial support by the Dept. of Defense
Keywords: Chemical weapons disposal -- United States; Chemical agents (Munitions) -- United States; Hazardous wastes -- Incineration -- United States; Incinerators -- United States -- Safety measures; Electronic books